Economics and policy implications of residential photovoltaic systems in Italy's developed market. (December 2022) - D'Adamo, Idiano; Gastaldi, Massimo; Morone, Piergiuseppe; Ozturk, Ilhan
Abstract: This work quantifies the economic advantage of a 110% versus a 50% subsidized tax deduction for installing new residential PV systems in Italy using net present value as an indicator. The results show that the percentage of self-consumed energy significantly impacts the profitability of these systems. The break-even point analysis identifies the values at which profitability occurs depending on different policy scenarios. In addition, it is pointed out that in some contexts, the economic benefits to the state are greater than those to the consumer in the scenario involving a different selling price. Highlights: Growth in renewables represents a crucial step towards achieving Sustainable Development Goals SDG7. A green transition in residential sector can be achieved through the application of photovoltaic energy. The percentage of self-consumed energy has a significant impact on the profitability of these systems. The economic benefits for the State exceed those of the consumer, the selling price of energy and the investment cost of PV systems. Supporting a green transformation of the residential sector over time – not only in Italy, but globally.